Panduan Praktikum Fisika Dasar 1 Berbasis Guided Inquiry Terhadap Peningkatan Hard Skills dan Soft Skills Mahasiswa - Suprianto Suprianto; S. Ida Kholida; Herman Jufri Andi (Universitas PGRI Kanjuruhan Malang, 2017)
Abstract This study aims to analyze the significant influence of the use of first basic physics guide based on a guided inquiry to increased hard skills and soft skills of students. The experimental design used was